Exploring artificial intelligence literacy among basic school teachers in Ghana - Valentina Arkorful; Francis Arthur; Eric Boateng; Monica Ofosu-Koranteng; Iddrisu Salifu; Emmanuel Rungson Attom; Solomon Adjatey Tetteh; Emmanuel Quayson; Stanley Asare-Bediako; Sharon Abam Nortey (Discover Education)
Abstract In the twenty-first century, it has become increasingly important for educators to familiarise themselves with “Artificial Intelligence (AI)”, given its growing influence in various fields, including education. This study examines AI literacy among Ghanaian basic school teachers and investigates gender differences in AI literacy. This study used a cross-sectional survey design to assess the AI literacy of 319 teachers using an adapted AI literacy scale. Data were analysed using descriptive statistics (mean and standard deviation) and “one-way multivariate analysis of variance (MANOVA)”. In addition, “confirmatory factor analysis (CFA)” was used to validate the adapted AI literacy scale. The results showed that overall, teachers had moderate levels of AI literacy. Specifically, they demonstrated moderate levels of “knowledge and understanding of AI”, “application of AI”, “evaluation of AI”, and “ethics of AI”. In addition, the results showed that gender differences in the dimensions of AI literacy were statistically significant. This article contributes to the literature on AI literacy among teachers by examining gender differences in dimensions of AI literacy. It further advances the field by discussing the implications of these findings for educational policy and practice, highlighting the need for targeted interventions to address the gender gap in AI literacy. By adding to the growing body of research on AI education, this research provides valuable insights for policymakers, educational administrators, and teacher preparation programmes aimed at improving AI literacy among educators.